BATIK NASKAH KUNO: TRANSFORMASI ILUMINASI DARI NASKAH KUNO KE DALAM MOTIF BATIK - Pandanwangi, Ariesa; Alya, Sophia Himatul; Budiman, Iman; Apin, Arleti Mochtar; Darmayanti, Tessa Eka (PANGGUNG, 2022)
Ancient manuscripts are artifacts that indicate high intellectual abilities in old civilizations. The content is very valuable as well as a means of communicating and expressing ideas that can provide information about civilization and past life. Javanese society is one of the communities who inherited ancient manuscripts. The manuscript is decorated with beautiful illuminations that signify the aesthetics of the creators. The illumination has a n implied value and becomes a trace of the cultural identity of the society. The values implied in the manuscript will be much more useful if it is disseminated to provide high moral understanding and insight. In addition, ancient manuscripts can be a source of inspiration for creation that can support efforts to perpetuate cultural heritage in the archipelago. This paper discusses the results of research originating from the transformation process of ancient manuscript illumination into batik. The research method used is descriptive qualitative by making batik motifs based on visual manuscript illumination supported by the results of interviews with ancient manuscript experts and batik experts. The results of this study are expected to support batik motifs in Indonesia. Keywords: ancient manuscripts; batik; illumination; motiftransformation